2017
DOI: 10.1159/000479422
|View full text |Cite
|
Sign up to set email alerts
|

Observational Monitoring of Patients with Aplastic Anemia and Low/Intermediate-1 Risk of Myelodysplastic Syndromes Complicated with Iron Overload

Abstract: Background: This study focuses on the iron overload (IOL) of patients with transfused aplastic anemia (AA) or a low/intermediate-1 risk of myelodysplastic syndrome (MDS). Methods: Ninety-two AA or MDS patients with IOL were prospectively recruited. Clinical data were collected every 6 months, and organ magnetic resonance imaging T2* values were collected annually. Patients with IOL were chelated. Results: Serum ferritin was correlated with liver T2* and pancreatic T2* in the AA and MDS groups. Transfusion amou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 31 publications
(39 reference statements)
1
10
0
Order By: Relevance
“…The accumulation of iron in organs of patients with MDS is a finding present in the disease, with the liver, heart and pancreas being the most affected organs [7,11].…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of iron in organs of patients with MDS is a finding present in the disease, with the liver, heart and pancreas being the most affected organs [7,11].…”
Section: Discussionmentioning
confidence: 99%
“…Du et al 12 "in the MDS group, no correlations were found between the transfusion amount and serum ferritin or MRI T2*" Frytak et al 13 "The economic burden of MDS is high for both transfusion-dependent and transfusion-independent patients, but can be especially onerous for those who are transfusion-dependent. "…”
Section: Survivalmentioning
confidence: 99%
“…Nine studies reported outcomes relating to iron overload and its complications. 10,12,19,24,27,30,32,37,43 Three studies found an increased risk of iron overload complications among transfused MDS patients, including presentations of cardiomyopathy/heart failure, conduction disorders, diabetes and liver disease. 10,27,30 Two studies examined magnetic resonance imaging evidence of iron deposition with conflicting results about the correlation between liver iron and transfusion burden.…”
Section: Clinical Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Myocardial iron overload (MIO) must be diagnosed with cardiac imaging techniques, because iron overload serum markers (ferritin and labile plasma iron) and/or the presence of hepatic siderosis do not correlate adequately with cardiac siderosis. 7) 8) T2* relaxation time measured by cardiac magnetic resonance (cMR) has become the gold standard parameter for the diagnosis and follow-up of these patients, 9) which is reduced in the presence of intramyocardial ferritin and hemosiderin.…”
Section: Introductionmentioning
confidence: 99%